Development of a Baseline Game Learning Model to Improve Field Tennis Learning Outcomes - Arif Haryanto; Tandiyo Rahayu; Taufiq Hidayah (STKIP Muhammadiyah Kuningan, 2023)
The aims of this research is (1) to unveil how is the product, (2) to discover the effectiveness of the learning model, and (3) to determine the acceptance response of baseline game product as a learning model in increasing tennis-learning outcome of students in Physical Sport and Recreation Study Program, Universitas Negeri Gorontalo. This is a Research and Development type of research where the subject of the research is the student of Physical Sport and Recreation Study Program, Universitas Negeri Gorontalo. Data of this research are product’s quality evaluation result, suggestion for product improvement, and students’ questionnaire result, which are obtained from expert evaluation, experimental study of small group (20 students), and experimental study of large group (50 students). The results of this study are a product of the baseline game learning model for tennis games. The results of the product assessment for the standard game learning model were 88 % (good) for small-scale trials and 93.13 % (good) for large scale trials. Based on the findings of the study and assessment, it can be said that the baseline game learning model for tennis games can be used to enhance the learning outcomes of field tennis for students enrolled in Physical Sport and Recreation Study Program, Universitas Negeri Gorontalo.